Women and in Anti-Corruption Eradication - Zamhur, Arista; Aulia, Nazwa; Nadia Putri, Astri; Gulo, Dewi Murni; Ariani, Nadia; Purwanti, Rahayu Desliana Dwi; Alhamdani, Muhammad Rizky (Jurnal Edukasi Terkini, 2025)
Purpose-The purpose of this study is to identify and analyze the role played by women in corruption in Indonesia. Research Methodology/Design/Approach-This research uses a library research method sourced from books and journals related to women and anti-corruption prevention. Finding-The results of this study show that anti-corruption programs targeting women, such as Saya Perempuan Anticorruption (SPAK) effectively increase women's awareness and participation in anti-corruption campaigns. Utilizing empirical data and theories related to this research shows that women have a very strategic approach in recognizing and combating corruption. there are various aspects of women's participation in anti-corruption efforts, ranging from domestic roles as caregivers and friends to active participation in anti-corruption organizations within the civil society. Originality / Value-The study shows that gender disparity is an important factor in reducing corruption rates because higher gender disparities result in lower levels of corruption.